The use of the flipped classroom strategy in learning Arabic literature among non-Arabic speaking students - Al-Khalidi, Evan Najeh; Toklubok, Pabiyah; Mustapha, Nik Farhan (Human Resources Management Academic Research Society (HRMARS), 2023)
Previous studies have highlighted the negative view of learning Arabic literature among non-native students due to the difficulty in understanding literary texts. To focus on changing this view, a need to change the method of teaching and learning literature is required. Scholars have emphasised that the flipped classroom strategy is proven to improve the level of traditional learning. Therefore, this study aims to identify the use of the flipped classroom strategy in learning literature among Malaysian students. A survey was conducted on 85 students majoring in Arabic study from three public universities in Malaysia. The findings of this study provide an insight of their acceptance and satisfaction with the flipped classroom in learning Arabic literature. The most positive feedback generated by the results is active learning that relies on interaction between the learners themselves and the trainer. Moreover, most of the respondents found that this strategy helps them in understanding the words and main ideas in the literary text. Several recommendations have been offered and are expected to be used to improve the teaching and learning of Arabic literature for non-Arabic speakers